A low-exothermic antibacterial and anti-inflammatory injectable bone cement and its preparation method
Through the combination of modified hydroxyapatite and polymethyl methacrylate prepolymerization liquid and the polymerization of the redox system, a low-exothermic antibacterial and anti-inflammatory injectable bone cement was prepared, which solved the problems of excessive exothermic and insufficient mechanical properties of the existing bone cement, and achieved safer and more effective bone repair.
Patent Information
- Application Number
- CN202310204560.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-06
AI Technical Summary
Excessive exothermic cement after implantation into the human body may cause tissue damage and necrosis. At the same time, the volume contraction and high elastic modulus during its curing process will affect bone healing and stress conduction, increasing the risk of wear and secondary damage.
Antibacterial and anti-inflammatory anti-inflammatory bone cement is used with low exothermic anti-inflammatory. The preparation method includes combining modified hydroxyapatite with polymethyl methacrylate prepolymerization solution, initiating polymerization through a redox system, controlling the maximum polymerization temperature below 37°C, and adding antibacterial and anti-inflammatory drugs to the bone cement to improve antibacterial and anti-inflammatory properties.
It effectively reduces the heat exogenous amount of bone cement during the polymerization process, avoids tissue damage, improves the mechanical properties and bone conductivity of bone cement, increases the antibacterial and anti-inflammatory effect, and reduces the stress changes of fracture pyramids and the risk of secondary damage.
Smart Images

Figure CN116139332B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to orthopedic medical materials, and in particular to low-exothermic antibacterial and anti-inflammatory injectable bone cement and a preparation method thereof. Background Art
[0002] In recent years, due to the aging of the population, bone defects and bone degeneration caused by osteoporosis and other bone-related diseases have been increasing, resulting in a sharp increase in the demand for bone repair materials. Bone cement, as a commonly used repair material in orthopedic surgery, can be filled in the gaps at the bone damage through minimally invasive implantation or injection, which has the effect of promoting bone healing.
[0003] Polymethyl methacrylate (PMMA) bone cement consists of two parts: powder phase and solidifying liquid. It exhibits good mechanical strength and injectability. It is currently the most widely used bone cement in clinical practice and has been widely used in artificial joints, repair of bone defect wounds, and cone compression fractures. However, PMMA bone cement still has some limitations in clinical application. First, after bone cement is implanted into the human body, the methyl methacrylate monomer and methyl methacrylate polymer mix and release heat. Local heat release will cause certain damage to the tissues around the human bones, which is easy to cause tissue damage and necrosis. Secondly, bone cement will produce a certain volume shrinkage during the curing process, resulting in loosening of the bond between the bone and the prosthesis, which has an adverse effect on normal stress conduction. At the same time, the elastic modulus of PMMA bone cement is too high, causing stress changes in the fracture cone, which will cause wear and even secondary damage to human bones.
[0004] Natural bone is mainly composed of nano-hydroxyapatite and collagen fibers. As a bioactive material with good biocompatibility, hydroxyapatite can form a good chemical bond with bone at the interface after being implanted into bone tissue, and has become one of the research hotspots of implant materials. Among them, many characteristics of hydroxyapatite are related to its particle size. Compared with ordinary HA, nano-hydroxyapatite (n-HA) has a higher surface area, greater surface energy, higher solubility and higher bioactivity, which is more similar to the properties of natural bone. Therefore, it is widely used in the practical application of bone filling materials. Although nano-hydroxyapatite (n-HA) has good biocompatibility, it lacks structural integrity and poor compatibility. The mechanical strength of bone cement prepared with hydroxyapatite as the main body is difficult to meet the requirements, which increases its challenge in practical application. When hydroxyapatite and polymer are compositely blended, their mechanical properties depend to a large extent on the interfacial bonding force between inorganic particles and polymers. Simple hydroxyapatite nanoparticles are easy to agglomerate and have poor adhesion to the polymer interface, resulting in poor mechanical properties.
[0005] In addition, after the filler is implanted, the implant is prone to bacterial infection over time. This situation can seriously affect the patient's comfort and even affect the patient's normal life. In addition, in the microenvironment of bone growth, higher reactive oxygen (such as H2O2 and OH·) and hypoxic environment also inhibit bone healing. Summary of the invention
[0006] The purpose of the present invention is to provide a low-exothermic antibacterial and anti-inflammatory injectable bone cement and a preparation method thereof, wherein a low-exothermic, antibacterial and anti-inflammatory injectable bone cement is prepared, each step of the reaction is safe and reliable, the operation is simple, and the conversion rate of each step is high.
[0007] In one aspect of the present invention, the present invention proposes a method for preparing injectable bone cement. According to an embodiment of the present invention, the method comprises the following steps:
[0008] S1. Prepare polymethyl methacrylate prepolymer solution: weigh methyl methacrylate and put it into a container, add initiator, shake it thoroughly until it is completely dissolved, heat it in a water bath, and shake the conical flask gently from time to time to observe the viscosity of the system until the viscosity of the system in the conical flask is close to that of glycerol, then take out the container, put it into cold water and cool it to room temperature to terminate the reaction;
[0009] S2. Using polymethyl methacrylate prepolymer and a certain amount of N,N-dimethylaniline as liquid phase and a certain proportion of modified hydroxyapatite and dibenzoyl peroxide as solid phase, the two phases are mixed and stirred until uniformly dispersed, and then placed in an oven and heated to solidify. After demolding, the antibacterial and anti-inflammatory injectable bone cement is obtained.
[0010] In addition, the method for preparing an injectable bone cement according to the above embodiment of the present invention may also have the following additional technical features:
[0011] In some embodiments of the present invention, in step S1, the initiator is dibenzoyl peroxide or azobisisobutyronitrile; the water bath temperature is 70-90° C. and the mass of the initiator is 0.5%-1.5% of the mass of the methyl methacrylate prepolymer solution.
[0012] In step S2, the mass ratio of liquid phase to solid phase is 1:0.05-0.25; the mass of dibenzoyl peroxide is 0.2%-1.5% of the mass of methyl methacrylate prepolymer liquid; the mass of N,N-dimethylaniline is 1%-3% of the mass of methyl methacrylate prepolymer liquid, and the oven temperature is 37°C.
[0013] In some embodiments of the present invention, in step S2, the modified hydroxyapatite is a mixture of hydroxyapatite modified by oxidized sodium alginate and polyethyleneimine and nano-hydroxyapatite modified by hydroxy-functional drugs, and the mass ratio of the hydroxyapatite modified by oxidized sodium alginate and polyethyleneimine to the nano-hydroxyapatite modified by hydroxy-functional drugs is 1:0.25-0.75.
[0014] In some embodiments of the present invention, the method for preparing oxidized sodium alginate and polyethyleneimine-modified hydroxyapatite comprises the following steps:
[0015] S201, placing nano-hydroxyapatite in a mixed solution of ethanol and deionized water, stirring the mixture by ultrasonic until dispersed, adding an excess of triaminopropyltriethoxysilane, stirring the mixture overnight, centrifuging the mixture, fully drying the mixture, and grinding the mixture with a mortar to obtain amino-modified hydroxyapatite;
[0016] The structural formula of amino-modified hydroxyapatite is as follows:
[0017]
[0018] The synthetic route of amino-modified hydroxyapatite is as follows:
[0019]
[0020] S202, dissolving oxidized sodium alginate in water to obtain an oxidized sodium alginate solution, adding amino-modified hydroxyapatite and polyethyleneimine under stirring, stirring overnight and freeze-drying, grinding with a mortar to obtain oxidized sodium alginate and polyethyleneimine-modified hydroxyapatite.
[0021] The structural formula of hydroxyapatite modified by oxidized sodium alginate and polyethyleneimine is as follows:
[0022]
[0023] The synthetic route of oxidized sodium alginate and polyethyleneimine modified hydroxyapatite is as follows:
[0024]
[0025] In some embodiments of the present invention, in step S201, the molar ratio of nano-hydroxyapatite to triaminopropyltriethoxysilane is 1:5-10, the volume ratio of ethanol to water is 9:1, the vacuum oven temperature is 50-80°C, and the drying time is 24-36h.
[0026] In the step S202, the mass ratio of the amino-modified hydroxyapatite, oxidized sodium alginate and polyethyleneimine is 1:0.5-0.8:0.2-0.5, the concentration of the oxidized sodium alginate solution is 0.05-0.2 g / mL, the freeze-drying temperature is -50°C, and the drying time is 48 hours.
[0027] In some embodiments of the present invention, the preparation method of oxidized sodium alginate includes the following steps: dissolving sodium alginate in deionized water, stirring thoroughly until dissolved to obtain a sodium alginate solution, adding sodium periodate to the sodium alginate solution, reacting for a certain period of time at room temperature in the dark, adding an appropriate amount of ethylene glycol to quench the reaction, placing it in a dialysis bag for thorough dialysis, and finally freeze-drying the dialysate to obtain oxidized sodium alginate.
[0028] The structure of oxidized sodium alginate is as follows:
[0029]
[0030] The synthetic route of oxidized sodium alginate is as follows:
[0031]
[0032] In some embodiments of the present invention, the concentration of sodium alginate is 0.02-0.03 g / mL, the molar ratio of sodium alginate to sodium periodate is 1:0.6-0.8, the reaction time is 4-6 h, the freeze-drying temperature is -50°C, and the drying time is 36 h.
[0033] In some embodiments of the present invention, the preparation method of the hydroxyl functional drug modified nano hydroxyapatite comprises the following steps: dissolving hydroxyapatite, hydroxyl functional drug and triethylamine in anhydrous tetrahydrofuran, injecting and adding a certain amount of oxalyl chloride under ice bath and nitrogen protection, transferring to room temperature and stirring overnight, filtering the suspension, washing until the supernatant is almost colorless, collecting the precipitate, vacuum drying, grinding and crushing with a mortar to obtain hydroxyl functional drug modified nano hydroxyapatite, wherein the hydroxyl functional drug is a drug containing active hydroxyl groups and having a promoting effect on bone healing.
[0034] In some embodiments of the present invention, the hydroxyl functional drug is one of dexamethasone, methylprednisolone, curcumin, gallic acid, dopamine, and perfluorononanol, the molar ratio of hydroxyapatite, hydroxyl functional drug, triethylamine and oxalyl chloride is 1:1-3:4.5:2-3, the ice bath stirring time is 30 minutes, and the reaction is carried out under light-proof conditions, the vacuum oven temperature is 35-50°C, and the drying time is 12-24 hours.
[0035] Among them, the structure of curcumin-modified nanohydroxyapatite HA-Cur is as follows:
[0036]
[0037] The synthetic route of curcumin-modified nanohydroxyapatite HA-Cur is as follows:
[0038]
[0039] In another aspect of the present invention, the present invention proposes a method for preparing a low-exothermic antibacterial and anti-inflammatory injectable bone cement, which is the same as the method for preparing the injectable bone cement, wherein the modified hydroxyapatite is a mixture of hydroxyapatite modified by oxidized sodium alginate and polyethyleneimine and nano-hydroxyapatite modified by hydroxyl functional drugs, the hydroxyl functional drugs are drugs containing active hydroxyl groups and having antibacterial and anti-inflammatory effects on bone healing, and the polymerization reaction temperature is lower than 37°C.
[0040] In another aspect of the present invention, the present invention provides a low exothermic antibacterial and anti-inflammatory injectable bone cement prepared by the preparation method of the low exothermic antibacterial and anti-inflammatory injectable bone cement.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1) The present invention prepares a variety of modified hydroxyapatite powders and polymethyl methacrylate prepolymer liquid with a viscosity similar to that of glycerol, takes polymethyl methacrylate prepolymer and N,N-dimethylaniline (DMA) as liquid phase, takes the above two modified hydroxyapatite powders (HA-Cur and HA-OSA-PEI) and dibenzoyl peroxide (BPO) as solid phase, mixes solid and liquid in a certain ratio, constructs a redox system, and prepares a low-exothermic, antibacterial and anti-inflammatory injectable bone cement. On the one hand, the bone cement is solidified by further polymerization induced by the redox system, and the maximum polymerization temperature is lower than 37°C, which is far lower than the 90°C requirement of the international standard for surgical implants-acrylic resin cement (ISO-5833). Compared with the prior art, the maximum temperature is generally above 70°C, which has been greatly reduced, effectively avoiding the problem of tissue damage and necrosis caused by a large amount of heat release during the polymerization process. On the other hand, adding active substance-modified hydroxyapatite to PMMA improves its osteoconductivity and degradation properties, and also improves the dispersibility of hydroxyapatite in polymethyl methacrylate polymer.
[0043] 2) The present invention prepares two types of hydroxyapatite powders modified with anti-inflammatory drug molecules, and increases their compatibility in polymethyl methacrylate prepolymer solutions. One is to connect curcumin (Cur) with nano-hydroxyapatite (n-HA) through oxalyl chloride to construct an oxalate bond that is sensitive to H2O2 at the bone growth site. The other is to react oxidized sodium alginate (OSA) with amino-modified nano-hydroxyapatite (n-HA-NH2) and polyethyleneimine (PEI) to construct a dynamic Schiff base bond that responds to the acidic environment at the bone growth site. The two modified hydroxyapatite powders can release the antibacterial and anti-inflammatory drugs curcumin (Cur) and polyethyleneimine (PEI) in response to the H2O2 microenvironment where bone growth is excessive, thereby improving the long-term antibacterial effect.
[0044] 3) The introduction of hydrophilic polymers oxidized sodium alginate (OSA) and polyethyleneimine (PEI) reduces the elastic modulus of bone cement, effectively reducing wear and secondary damage caused by stress changes in the fracture cone while maintaining good mechanical properties; secondly, it can also act as a hydrophilic channel, breaking the oxalate bond and Schiff base bond buried in the bone cement, promoting the release of internal drugs, and forming more porous structures after drug release, which is conducive to tissue colonization and angiogenesis; on the other hand, it has hygroscopicity, which can inhibit the loosening of the bond between bone cement and bones caused by volume shrinkage to a certain extent. At the same time, polyethyleneimine also has good cell adhesion, which is conducive to the colonization of osteoblasts.
[0045] 4) The surface of bone cement has a microporous structure, which is conducive to the colonization and angiogenesis of tissues. Bone cement has a certain water absorption, which prevents the loosening of the bond between bone and bone caused by the volume shrinkage of bone cement to a certain extent. In addition, the bone cement prepared by the present invention has good biocompatibility, fluidity and injectability, and has good adhesion at the bone tissue, and has good clinical application prospects.
[0046] 5) The present invention can connect hydroxyl functional drugs and hydroxyapatite through oxalate bonds, modify hydroxyapatite, and impart other properties, with good ductility. For example, dexamethasone and methylprednisolone can enhance their anti-inflammatory properties; gallic acid and dopamine can be used to enhance their antibacterial properties; perfluorononanol can be used to improve the hypoxic microenvironment by increasing oxygen supply to promote bone repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 FTIR spectra of hydroxyapatite (HA), curcumin (Cur) and hydroxyapatite grafted curcumin (HA-Cur) in Example 1 of the present invention;
[0048] Figure 2FTIR spectra of hydroxyapatite (HA) and hydroxyapatite (HA-NH2) modified with triaminopropyltriethoxysilane in Example 1 of the present invention;
[0049] Figure 3 is the hydrogen nuclear magnetic resonance spectrum of sodium alginate and oxidized sodium alginate in Example 1 of the present invention;
[0050] Figure 4 FTIR spectra of hydroxyapatite (HA-NH2) modified with triaminopropyltriethoxysilane, oxidized sodium alginate (OSA) and the reaction product (HA-OSA) of the two in Example 1 of the present invention;
[0051] Figure 5 FTIR spectra of HA-OSA, polyethyleneimine (PEI) and the product HA-OSA-PEI after the reaction of the two in Example 1 of the present invention;
[0052] Figure 6 The thermogravimetric diagram of HA and HA-Cur in Example 1 of the present invention;
[0053] Figure 7 The dough time diagram of the bone cement in Example 1 is measured according to the international standard of surgical implants--acrylic resin cement (ISO-5833) of the present invention;
[0054] Figure 8 The temperature-time diagram of the bone cement in Example 1 is measured according to the international standard of surgical implants--acrylic resin cement (ISO-5833) of the present invention;
[0055] Fig. 9 The setting time diagram of the bone cement in Example 1 is measured according to the international standard of surgical implants--acrylic resin cement (ISO-5833) of the present invention;
[0056] Fig.10 The bending modulus diagram of the bone cement in Example 1 and Example 2 is measured according to the international standard for measuring surgical implants--acrylic resin cement (ISO-5833) of the present invention;
[0057] Fig.11 In the figure, (a) is a graph of the compressive strength of the bone cement in Example 1 and Example 2 measured according to the international standard of surgical implants--acrylic resin cement (ISO-5833) of the present invention, and (b) is a graph of the elastic modulus of the bone cement in Example 1 and Example 2 of the present invention;
[0058] Fig.12 This is a graph showing the cumulative release rate of curcumin in the H2O2 microenvironment of the bone cement of the test group 4 in Example 1 of the present invention;
[0059] Fig.13Graph showing the antioxidant properties of the bone cement of test group 4 in Example 1 of the present invention;
[0060] Fig.14 Figure 1 is a graph showing the injectability and bone adhesion of the bone cement of the test group 2 in Example 1 of the present invention;
[0061] Fig.15 The bone cements in Example 1 and Example 2 of the present invention are immersed in simulated body fluid (SBF) for 10 days, and their weight loss rate is measured by weighing their dry weight;
[0062] Fig.16 The bone cements in Examples 1 and 2 of the present invention were immersed in simulated body fluid (SBF) for 10 days, and the porosity of the bone cements was measured by Archimedes' hair-splitting. DETAILED DESCRIPTION
[0063] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] Example 1
[0065] A method for preparing a low-exothermic antibacterial and anti-inflammatory injectable bone cement comprises the following steps:
[0066] (1) Preparation of HA-Cur:
[0067] Dissolve 1g of nanohydroxyapatite (n-HA), 0.73g of curcumin (Cur) and 0.9g of triethylamine (TEA) in 20mL of anhydrous THF, fill with nitrogen and stir in an ice bath for 10min. Dissolve 0.75g of oxalyl chloride in 3.6ml of THF and slowly add it to the above solution with a syringe. After stirring in an ice bath for 30min, transfer to room temperature and stir overnight. Filter the suspension, wash with dichloromethane until the supernatant is almost colorless, collect the precipitate, dry it in a vacuum at 40℃ for 24h, and grind it in a mortar to obtain an orange-red solid powder HA-Cur. Figure 1 As shown, by 1760cm -1 The carbonyl absorption peak at 147° proved that HA and Cur were successfully cross-linked through oxalate bonds. Figure 6 As shown, the grafting rate of curcumin was calculated to be 45.6%.
[0068] (2) Preparation of HA-OSA-PEI:
[0069] a. Preparation of oxidized sodium alginate:
[0070] Dissolve 6g of sodium alginate in 200ml of deionized water and stir thoroughly until dissolved. Dissolve 4.75g of NaIO4 in 20ml of deionized water and slowly add it dropwise to the above sodium alginate solution through a separatory funnel. After reacting for 6h at room temperature in the dark, add 3ml of ethylene glycol to quench the reaction. Put it into a dialysis bag with a molecular weight cutoff of 3000Da and dialyze it thoroughly. Finally, freeze-dry the dialyzate for 48h to obtain a white product, oxidized sodium alginate (OSA). Figure 3 As shown in the figure, the newly generated aldehyde peak and hemiacetal peak after the reaction prove that the oxidation of sodium alginate is successful.
[0071] b. Amino modification of hydroxyapatite:
[0072] Place 2g of nano-hydroxyapatite (n-HA) in 100ml of a mixed solution of CH3CH2OH:H2O=9:1 (v / v), and stir thoroughly with ultrasound until dispersed. Add 8g of triaminopropyltriethoxysilane (ATPES), stir overnight, centrifuge, wash with dichloromethane 5 times, dry in a vacuum oven for 48h, and grind with a mortar to obtain a white powder, which is amino-modified hydroxyapatite HA-NH2. Figure 2 As shown, by 2925cm -1 and 2960cm -1 The absorption peak of the methylene group at the 40°C region proves the successful connection of the silane coupling agent.
[0073] c. Synthesis of HA-OSA-PEI:
[0074] Dissolve 1.76g of oxidized sodium alginate (OSA) in 15ml of deionized water. After it is fully dissolved, add 4.15g of amino-modified hydroxyapatite (HA-NH2) and 0.52g of polyethyleneimine (PEI) under stirring. Stir at room temperature overnight and freeze-dry for 48h. Grind with a mortar to obtain light yellow hydroxyapatite powder HA-OSA-PEI. Figure 4 As shown, after the reaction, the -1 There are two peaks at , one of which is the bending vibration peak of the hydroxyl group and the other is the absorption peak of the Schiff base bond, proving the successful grafting of oxidized sodium alginate. Figure 5 As shown, after the reaction, 3310cm -1 The amino absorption peak and 1450 cm -1 The bending vibration peak of the methylene group proves the successful grafting of polyethyleneimine.
[0075] (3) Preparation of polymethyl methacrylate prepolymer liquid: Weigh 20 g of methyl methacrylate into a conical flask, add 120 mg of dibenzoyl peroxide (BPO), shake thoroughly until completely dissolved, heat in a water bath at 85°C, and gently shake the conical flask intermittently to observe the viscosity of the system until the viscosity of the system in the conical flask is similar to that of glycerol. Then, take out the conical flask, put it in cold water and cool it to room temperature to terminate the reaction.
[0076] (4) Preparation of bone cement: 5 g of polymethyl methacrylate prepolymer and 60 mg of N,N-dimethylaniline (DMA) were used as the liquid phase, and 20 mg of dibenzoyl peroxide (BPO) and two modified hydroxyapatites (the mass ratio of HA-Cur and HA-OSA-PEI was 3:7) were used as the solid phase, wherein the contents of the two modified hydroxyapatites are shown in Table 1. The two phases were mixed and stirred until uniformly dispersed, and then placed in an oven at 37°C and heated until solidified. After demolding, the final bone cement (HA / PMMA) was obtained.
[0077] Table 1 Mass addition of HA-Cur and HA-OSA-PEI in Example 1
[0078] Experimental Group 1 Experimental Group 2 Experimental Group 3 Experimental Group 4 The mass percentage of solid phase 5% 10% 15% 20% Quality of HA-Cur 75mg 150mg 225mg 300mg Quality of HA-OSA-PEI 175mg 350mg 525mg 700mg
[0079] like Figure 7 As shown in Table 1, the four test results all meet the requirement of 3-5min dough time in the international standard for surgical implants - acrylic resin cement (ISO-5833). Figure 8 As shown in Table 1, the highest temperatures of the four groups of experiments during the polymerization process were all lower than human body temperature, which effectively avoided the problem of tissue damage and necrosis caused by the large amount of heat released by bone cement during the polymerization process. Fig. 9 As shown in Table 1, the setting time of the four test groups is less than 15 minutes, which meets the requirements of the international standard for surgical implants - acrylic resin cement (ISO-5833).
[0080] like Fig.12 As shown, the bone cement in the test group 4 was placed in a 10 mM H2O2 solution, and the cumulative release rate of the 20% group of curcumin in Example 1 was calculated by the change of the absorption peak at 425 nm of the UV-visible absorption spectrum. After 7 days, the cumulative release rate of curcumin reached 88.7%.
[0081] like Fig.13 As shown, the bone cement in test group 4 was placed in hydrogen peroxide solutions of different concentrations (1 mM and 10 mM), and the quenching rate of DPPH was calculated by the change of the absorption peak at 517 nm of the UV-visible absorption spectrum. As the hydrogen peroxide concentration increased and the time prolonged, the DPPH free radical scavenging rate also gradually increased, indicating that it has good antioxidant properties and can be used to scavenge excess free radicals generated in the bone healing microenvironment.
[0082] like Fig.14 As shown, the bone cement slurry of the test group 2 after initial mixing was injected through a syringe, indicating that it had good injectability and adhesion.
[0083] Example 2
[0084] A method for preparing a low-exothermic antibacterial and anti-inflammatory injectable bone cement comprises the following steps:
[0085] (1) Preparation of HA-Cur: Dissolve 1.5 g of nanohydroxyapatite (n-HA), 0.88 g of curcumin (Cur) and 1.1 g of triethylamine (TEA) in 30 ml of anhydrous THF, fill with nitrogen and stir in an ice bath for 10 min. Dissolve 0.91 g of oxalyl chloride in 4.5 ml of THF and slowly add it to the above solution with a syringe. After stirring in an ice bath for 30 min, transfer to room temperature and stir overnight. Filter the suspension, wash with dichloromethane until the supernatant is almost colorless, collect the precipitate, dry it in a vacuum at 40°C for 24 h, and grind it in a mortar to obtain an orange-red solid powder HA-Cur.
[0086] (2) Preparation of HA-OSA-PEI:
[0087] a. Preparation of oxidized sodium alginate:
[0088] Dissolve 5 g of sodium alginate in 200 ml of deionized water and stir thoroughly until dissolved. Dissolve 2.96 g of NaIO4 in 15 ml of deionized water and slowly add it dropwise to the above sodium alginate solution through a separatory funnel. React at room temperature in the dark for 4 h. Add 3 ml of ethylene glycol to quench the reaction, then put it into a dialysis bag with a molecular weight cutoff of 3000 Da and dialyze it thoroughly. Finally, freeze-dry the dialyzate for 48 h to obtain a white product, oxidized sodium alginate (OSA).
[0089] b. Amino modification of hydroxyapatite:
[0090] 10 g of triaminopropyltriethoxysilane (ATPES) was placed in a mixed solution of 120 ml of CH3CH2OH:H2O=9:1 (v / v), and ultrasonicated and fully stirred until fully hydrolyzed. 3 g of nanohydroxyapatite (n-HA) was added to the above solution, stirred overnight and then centrifuged. After washing with dichloromethane 5 times, it was placed in a vacuum oven and dried for 48 hours, and ground with a mortar to obtain white powder HA-NH2.
[0091] c. Synthesis of HA-OSA-PEI:
[0092] Dissolve 1.42 g of oxidized sodium alginate (OSA) in 14 ml of deionized water. After it is fully dissolved, add 3.36 g of amino-modified hydroxyapatite (HA-NH2) and 0.32 g of polyethyleneimine (PEI) under stirring. Stir at room temperature overnight and freeze-dry for 48 hours. Grind with a mortar to obtain light yellow hydroxyapatite powder HA-OSA-PEI.
[0093] (3) Preparation of polymethyl methacrylate prepolymer liquid: Weigh 16 g of methyl methacrylate into a conical flask, add 75 mg of azobisisobutyronitrile (AIBN), shake thoroughly until completely dissolved, heat in a 75°C water bath, and gently shake the conical flask intermittently to observe the viscosity of the system until the viscosity of the system in the conical flask is similar to that of glycerol. Then, take out the conical flask, put it in cold water and cool it to room temperature to terminate the reaction.
[0094] (4) Preparation of bone cement: 4 g of polymethyl methacrylate prepolymer and 65 mg of N,N-dimethylaniline (DMA) were used as the liquid phase, and 20 mg of dibenzoyl peroxide (BPO) and two modified hydroxyapatites (the mass ratio of HA-Cur and HA-OSA-PEI was 4:6) were used as the solid phase, wherein the contents of the two modified hydroxyapatites are shown in Table 2. The two phases were mixed and stirred until uniformly dispersed, and then placed in an oven at 37°C and heated until solidified, and the final bone cement was obtained after demolding.
[0095] Table 2 Mass addition of HA-Cur and HA-OSA-PEI in Example 2
[0096] The mass percentage of solid phase 5% 10% 15% 20% Quality of HA-Cur 80mg 160mg 240mg 320mg Quality of HA-OSA-PEI 120mg 240mg 360mg 480mg
[0097] The strength of bones in different parts of the human body (such as femur, tibia, humerus) also varies. The content of the filling phase can be selected and adjusted according to the different parts of the human body to prepare bone cement with appropriate mechanical strength. Fig.10 As shown, multiple groups of bone cements in Example 1 and Example 2 were made into rectangular parallelepiped strips with a length of 75 mm, a width of 10 mm, and a height of 3.3 mm. The strength of multiple groups of tests reached the requirement of more than 50 MPa in the international standard for surgical implants - acrylic resin cement (ISO-5833), and had good bending resistance. Fig.11 As shown, multiple groups of bone cements in Example 1 and Example 2 were made into cylindrical splines with a diameter of 6 mm and a height of 12 mm. The strength of multiple groups of tests reached the 70 MPa requirement of the international standard for surgical implants - acrylic resin cement (ISO-5833), maintaining good compressive properties. At the same time, the elastic modulus is relatively small, which effectively avoids the wear of normal human bones caused by the change of stress of the fracture cone and adjacent cones due to the high elastic modulus, and even the harm of secondary fracture. Fig.15As shown, the weight loss rate of each group of experiments in Example 1 and Example 2 is very low, indicating that the bone cement can still maintain structural integrity after being immersed in the human body for many days and has good anti-collapse ability. Fig.16 As shown in the figure, with the increase of solid content, the porosity of bone cement also increases, and its pores are conducive to the colonization of capillaries.
[0098] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing injectable bone cement, characterized in that: The following steps are involved: S1. Prepare polymethyl methacrylate prepolymer liquid: weigh methyl methacrylate and put it into a container, add initiator, shake it thoroughly until it is completely dissolved, heat it in a water bath, and shake the conical flask gently from time to time to observe the viscosity of the system, until the viscosity of the system in the conical flask is close to that of glycerol, take out the container, put it into cold water and cool it to room temperature to terminate the reaction; S2. Using polymethyl methacrylate prepolymer and a certain amount of N,N-dimethylaniline as liquid phase and a certain proportion of modified hydroxyapatite and dibenzoyl peroxide as solid phase, the two phases are mixed and stirred until uniformly dispersed, and then placed in an oven and heated to solidify. After demolding, the injectable bone cement is obtained, wherein the modified hydroxyapatite is a mixture of oxidized sodium alginate and polyethyleneimine-modified hydroxyapatite and hydroxy-functional drug-modified nano-hydroxyapatite, and the mass ratio of the oxidized sodium alginate and polyethyleneimine-modified hydroxyapatite to the hydroxy-functional drug-modified nano-hydroxyapatite is 1:0.25-0.
75.
2. A method for preparing injectable bone cement according to claim 1, characterized in that: In the step S1, the initiator is dibenzoyl peroxide or azobisisobutyronitrile; the water bath temperature is 70-90° C.; the mass of the initiator is 0.5%-1.5% of the mass of the methyl methacrylate prepolymer solution; In step S2, the mass ratio of liquid phase to solid phase is 1:0.05-0.25; the mass of dibenzoyl peroxide is 0.2%-1.5% of the mass of methyl methacrylate prepolymer liquid; the mass of N,N-dimethylaniline is 1%-3% of the mass of methyl methacrylate prepolymer liquid; and the temperature of the vacuum oven is 37°C.
3. The method for preparing an injectable bone cement according to claim 1, characterized in that: The preparation method of the oxidized sodium alginate and polyethyleneimine-modified hydroxyapatite comprises the following steps: S201, placing nano-hydroxyapatite in a mixed solution of ethanol and deionized water, stirring the mixture by ultrasonic until dispersed, adding an excess of triaminopropyltriethoxysilane, stirring the mixture overnight and then centrifuging the mixture, drying the mixture thoroughly, and grinding the mixture with a mortar to obtain amino-modified hydroxyapatite; S202, dissolving oxidized sodium alginate in water to obtain an oxidized sodium alginate solution, adding amino-modified hydroxyapatite and polyethyleneimine under stirring, stirring overnight and freeze-drying, grinding with a mortar to obtain oxidized sodium alginate and polyethyleneimine-modified hydroxyapatite.
4. A method for preparing injectable bone cement according to claim 3, characterized in that: In the step S201, the molar ratio of nano-hydroxyapatite to triaminopropyltriethoxysilane is 1:5-10, the volume ratio of ethanol to water is 9:1, the vacuum oven temperature is 50-80°C, and the drying time is 24-36h; In the step S202, the mass ratio of the amino-modified hydroxyapatite, oxidized sodium alginate and polyethyleneimine is 1:0.5-0.8:0.2-0.5, the concentration of the oxidized sodium alginate solution is 0.05-0.2 g / mL, the freeze-drying temperature is -50°C, and the drying time is 48 hours.
5. The method for preparing an injectable bone cement according to claim 3, characterized in that: The preparation method of oxidized sodium alginate comprises the following steps: dissolving sodium alginate in deionized water, stirring thoroughly until dissolved to obtain a sodium alginate solution, adding sodium periodate to the sodium alginate solution, reacting for a certain period of time in the dark at room temperature, adding an appropriate amount of ethylene glycol to quench the reaction, putting the solution into a dialysis bag for thorough dialysis, and finally freeze-drying the dialysate to obtain oxidized sodium alginate, wherein the concentration of the sodium alginate is 0.02-0.03 g / mL, the molar ratio of the sodium alginate to the sodium periodate is 1:0.6-0.8, the reaction time is 4-6 hours, the freeze-drying temperature is -50°C, and the drying time is 36 hours.
6. The method for preparing an injectable bone cement according to claim 1, characterized in that: The preparation method of the hydroxyl functional drug modified nano hydroxyapatite comprises the following steps: dissolving hydroxyapatite, hydroxyl functional drug and triethylamine in anhydrous tetrahydrofuran, injecting and adding a certain amount of oxalyl chloride under ice bath and nitrogen protection, transferring to room temperature and stirring overnight, filtering the suspension, washing until the supernatant is nearly colorless, collecting the precipitate, vacuum drying, grinding and crushing with a mortar to obtain the hydroxyl functional drug modified nano hydroxyapatite, wherein the hydroxyl functional drug is a drug containing active hydroxyl groups and having a promoting effect on bone healing.
7. A method for preparing injectable bone cement according to claim 6, characterized in that: The hydroxyl functional drug is one of dexamethasone, methylprednisolone, curcumin, gallic acid, dopamine, and perfluorononanol. The molar ratio of hydroxyapatite, hydroxyl functional drug, triethylamine, and oxalyl chloride is 1:1-3:4.5:2-3. The ice bath stirring time is 30 minutes. The reaction must be carried out in a light-proof condition. The vacuum oven temperature is 35-50°C and the drying time is 12-24 hours.
8. A method for preparing a low exothermic antibacterial and anti-inflammatory injectable bone cement, characterized in that: The preparation method is the same as the preparation method of the injectable bone cement described in any one of claims 1 to 7, wherein the modified hydroxyapatite is a mixture of hydroxyapatite modified by oxidized sodium alginate and polyethyleneimine and nano-hydroxyapatite modified by a hydroxyl functional drug, the hydroxyl functional drug is a drug containing active hydroxyl groups and having antibacterial and anti-inflammatory effects on bone healing, and the polymerization reaction temperature of the two-phase mixing in step S2 is lower than 37°C.
9. A low exothermic antibacterial and anti-inflammatory injectable bone cement prepared by the method for preparing the low exothermic antibacterial and anti-inflammatory injectable bone cement according to claim 8.
Citation Information
Patent Citations
High-activity component PMMA-based bone cement capable of being quickly cured and preparation method and application thereof
CN112494721A
Cited By
Hydroxyapatite super-long nanowire / poly(methyl methacrylate) composite bone cement, and preparation method and application thereof
CN122805883A